FOPDT Model Based on Experimental Data from Municipal Solid Waste Incineration Process Temperature Control in Fixed Bed - Ainie Khuriati (Diponegoro University Semarang Indonesia, 2022)
Incineration is the waste combustion at controlled high temperatures which converts waste into flue gas with the main components being CO2 and water. Temperature control aims to ensure safe combustion operation. In this study, the temperature controller uses a two-position temperature controller whose main components include two thermocouples, MAX6675, two burners, blower, Arduino, and one laptop. Temperature controllers were used to maintain the temperature in the combustion chamber and afterburner at the specified setpoint, namely 630oC and 850oC, respectively. To test the performance of the controller, two models were made. The modeling was made using the experimental data obtained. The results show that the model and experimental results are in good agreement.